중생 복합내병성 고품질 벼 ‘청운’ - 최임수(Im-Soo Choi); 조영찬(Young-Chan Cho); 원용재(Yong-Jae Won); 김명기(Myeong-Ki Kim); 이점호(Jeom-Ho Lee); 이정희(Jeong-Heui Lee); 양창인(Chang-Ihn Yang); 김연규(Yeon-Gyu Kim); 김정주(Jeong-Ju Kim); 신영섭(Young-Seop Shin); 백만기(Man-Kee Baek); 이상복(Sang-Bok Lee); et al. (Korean journal of breeding, 2015)
The ‘Cheongun’ is a rice variety derived from a cross between ‘Suweon462’ which has translucent milled rice and medium maturity and ‘Milyang192’ that the elite line has a bacterial blight resistance and mid-late maturing property by the rice breeding team at NICS, RDA in 2012. The heading date of ‘Cheongun’ is August 13 and five days later than check variety, ‘Hwaseong’. It has 87 cm of culm length and 114 spikelets per panicle. It showed weaker cold tolerance than that of ‘Hwaseong’while exposed to cold stress. ‘Cheongun’ showed resistance to blast disease, K1, K2 and K3 race of bacterial blight and stripe virus, but susceptible to K3a race, other viruses and planthoppers. The milled rice of this variety exhibits translucent, clear non-glutinous endosperm and short grain shape. It has similar protein content (6.7%) and amylose content (19.5%) to that of ‘Hwaseong’. ‘Cheongun’ showed better palatability index of cooked rice than that of ‘Hwaseong’. Its milled rice recovery rate is similar to those of ‘Hwaseong’. However, whole grain rate of milled rice is higher than that of ‘Hwaseong’. ‘Cheongun’ has 4.98 MT/ha of milled rice productivity in ordinary cultivation. ‘Cheongun’ could be adaptable to the middle plain area in Korea (Registration No. 5114).